Зимівниківська мезолітична культура Лівобережної України - Залізняк, Л.Л.; Гавриленко, І.М. (Археологія, 1996)
Стаття присвячена новій мезолітичній культурі лісостепової смуги Лівобережної України. На прикладі матеріалів стоянки В'язівок 4а, докладно розглядається крем'яний інвентар, проблеми хронології та періодизації зимівниківських пам'яток на тлі мезоліту Східної Європи. Статья посвящена описанию нового культурного единства каменного века Украины, получившего название зимовниковская культура. Свыше десятка зимовниковских памятников открыто в лесостепном Левоберсжье Днепра и бассейне Северского Донца. Характеристика кремневого инвентаря, хозяйства, обряда жизни населения зимовниковской культуры дается на основе материалов исследования стоянки Вязовок 4а, которая исследовалась под Лубнами. На широком фоне восточно-европейского мезолита рассматриваются проблемы периодизации и хронологии культуры. Авторы пришли к выводу об их родстве с песочноровскими стоянками бассейна Десны, а также усть-камской культуры Среднего Поволжья. Вероятно, зародившись в Дриасе ІІІ, культура развивалась в раннем голоцене. The new culture of the stone age of Ukraine named the Zimovniki culture is described. Over a dozen of Zimovniki relics is excavated in the forest-steppe Left-bank area of the Dnieper and in the Basin of the Seversky Donets. Flint stocks, utensils, mode of life of the population in the period of the Zimovniki culture are characterized on the basis of findings from settlement Vyazovok-4a excavated near the town of Lubny. Problems of periodization and chronology of the culture are described on the background of the east—European Mesolithic age. The authors came to the conclusion on their affinity with Pesochnorovian sites of the Desna river basin and with Ust-Kama culture of the mid-Volga banks. Apparently, the culture being arisen in Drias III continued developing in early Holocene.